Development and evaluation of continuous inshelled walnut processing system. (8th February 2022) - Hussain, Syed Zameer; Naseer, Bazila; Qadri, Tahiya; Reshi, Monica; Amin, Tawheed; Kanojia, Varsha
Abstract: Walnut is one of the high yielding fruit crops grown in union territory of Jammu and Kashmir (J&K) in India. However, processing of walnuts in J&K is being carried out manually, which is very tedious, troublesome, and time and labor consuming. Thus, the present work was undertaken with an aim to develop a single mechanized continuous system for post‐harvest handling and processing of walnuts. The innovation composed of dehulling, bleaching, washing, drying, and grading units, besides conveyors to carry walnuts from one unit to another. The dehulling efficiency (95.70%), bleaching efficiency (96.28%), washing efficiency (99.10%), and grading efficiency (97.43%) recorded for the developed system are much higher than the manual processing. Furthermore, number of partially dehulled, un‐dehulled, partially bleached, unbleached, and damaged walnut percentages were recorded significantly ( p  < 0.05) lower whereas fully dehulled and fully bleached walnut percentages were recorded significantly ( p  < 0.05) higher in case of developed system as compared with manual processing. Overall capacity and efficiency of the developed system were recorded as 800 kg/day and 97.02%, respectively. The labor requirement for processing 1 ton of walnuts using developed system was determined to be 10 man h. The economic analysis indicated that adoption of developed system for walnut processing can be highly beneficial and economic. Thus, developed system can be a feasible alternative to minimize the post‐harvest losses, to maintain the quality, and to overcome the drudgery, boredom, and constraints associated with manual post‐harvest handling and processing of walnuts. Practical Applications: Jammu and Kashmir (J&K) has the largest share in India's total walnut production. However, from the last few years, there has been a setback to the export trade potential of walnuts in India, mainly due to import of walnuts from China and California. The walnuts from California and China have better consumer acceptability than walnuts of J&K, which has badly affected the walnut trade in India. In J&K, post‐harvest handling of walnuts is being done manually without any scientific and mechanical arbitration, which leads to quality deterioration of walnuts. Therefore, in order to compete at international level, there is an immediate need to shift the post‐harvest handling of walnuts from manual to mechanized. Thus, the adoption of developed continuous inshelled walnut processing system can play a vital role in sustaining the rural economy of J&K through production and sale of good quality walnuts. Furthermore, the developed system can serve as a benchmark for establishment of modern walnut processing units, which can lead to employment generation and boost the walnut trade in J&K. Abstract : In order to overcome the constraints associated with manual walnut processing, a continuous inshelled walnut processing system was designed and developed. The system has a capacity of 800 kg/day and efficiency of 97.02%, however manually a person processes around 40 kgs of walnuts per day with an efficiency of 80‐85%. Adoption of developed system can drastically reduce labour requirement to 10 mannhours/ton as compared to 200 mannhours/ton for manual walnut processing.